Centres and Peripheries as an Analytical and Conceptual Framework - Kwarcińska, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The aim of the article is to investigate the centre – periphery framework for its practical usefulness as an analytical and explanatory tool to study the processes of space, cultural (including symbolic), political, and economic concentration and polarisation.There are two parts. The first examines theoretical problems concerning the application of the centre and periphery. The issues discussed include the fact that these concepts can be arbitrary, while there are many tacit additional assumptions surrounding the concepts of centre and periphery, which seem to make up a universal conceptual framework. The second part investigates the possibility of making a clear typology of centres and peripheries based the dominant processes and observable phenomena that make up the processes (examples are given for some of them). The article is a kind of metatheoretical overview and aims to identify further directions of centres-periphery research.As a result of the analysis, a list of observable categories comprising the description of centres and peripheries was made. These categories can be the foundation of a typologisation and operationalisation in empirical research. The concept of „periphery compensation” is of particular significance. It confirms the status of peripheries and reveals the direction of a dominant relation.